2014
DOI: 10.1111/imm.12293
|View full text |Cite
|
Sign up to set email alerts
|

CXCR3 deficiency enhances tumor progression by promoting macrophage M2 polarization in a murine breast cancer model

Abstract: SummaryTumor associated macrophages play a vital role in determining the outcome of breast cancer. We investigated the contribution of the chemokine receptor CXCR3 to antitumor immune responses using a cxcr3 deficient mouse orthotopically injected with a PyMT breast cancer cell line. We observed that cxcr3 deficient mice displayed increased IL-4 production and M2 polarization in the tumors and spleens compared to WT mice injected with PyMT cells. This was accompanied by larger tumor development in cxcr3 À/À th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 40 publications
4
65
2
Order By: Relevance
“…That said, however, it is not clear why early-stage infection was better controlled in CXCL10 Ϫ/Ϫ mice than CXCR3 Ϫ/Ϫ mice, although mice of both backgrounds showed similarly deficient initial mononuclear cell recruitment. Possible explanations might involve CXCL10's CXCR3-independent actions unrelated to chemotaxis (61), CXCR3 effects unrelated to CXCL10 (19,62), or a predisposition of CXCR3-deficient macrophages toward an alternatively activated (M2) state (63).…”
Section: Discussionmentioning
confidence: 99%
“…That said, however, it is not clear why early-stage infection was better controlled in CXCL10 Ϫ/Ϫ mice than CXCR3 Ϫ/Ϫ mice, although mice of both backgrounds showed similarly deficient initial mononuclear cell recruitment. Possible explanations might involve CXCL10's CXCR3-independent actions unrelated to chemotaxis (61), CXCR3 effects unrelated to CXCL10 (19,62), or a predisposition of CXCR3-deficient macrophages toward an alternatively activated (M2) state (63).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the phenotype of these cells was most consistent with the reported phenotype of TNFa and iNOS-producing DCs (TIP-DC; refs. [36][37][38]. Although these cells are called "TIP-DCs," it has been suggested that these cells can be considered inflammatory macrophages (38).…”
Section: Ly6cmentioning
confidence: 99%
“…A recent study showed that CXCR3 expression was important for macrophage polarization in a murine breast cancer model. The study demonstrated that the absence of host CXCR3 expression led to increased tumor growth and progression with enhanced levels of TAMs with M2 polarization [26]. The absence of macrophage CXCR3 expression led to M2 polarization and regulated innate and immune cell-mediated anti-tumor responses that present important therapeutic implications for breast cancer.…”
Section: Introductionmentioning
confidence: 93%